Metropoles économiques.... [1ère série], Londres, Amsterdam, Anvers, Liège, Francfort, Mannheim, Nuremberg, Linz, Barcelone, Gênes, Naples, New-York - Chardonnet, Jean (1914?-1996)
cartes, plans, couv. ill.